2009
DOI: 10.1097/nmd.0b013e3181923ca1
|View full text |Cite
|
Sign up to set email alerts
|

Validity of DSM-IV Axis V Global Assessment of Relational Functioning Scale

Abstract: We investigate the convergent validity of the DSM-IV Axis V Global Assessment of Relational Functioning Scale (GARF; American Psychiatric Association, 1994). This study included 79 patients at a university-based outpatient treatment clinic. We examined clinician-rated GARF and the relationship to self-reported (Inventory of Interpersonal Problems; IIP-C; Horowitz et al. 2000) and free response themes [Social Cognition and Object Relations Scale: SCORS; Hilsenroth, Stein & Pinsker, 2004; Westen, 1995] of interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…This provides convergent validity as similar results were found in past SCORS-G research (Stein, Hilsenroth, Pinsker-Aspen, & Primavera, 2009). We would expect that those who have healthier self and interpersonal functioning capacities would lead to better coping capacities and overall functioning.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This provides convergent validity as similar results were found in past SCORS-G research (Stein, Hilsenroth, Pinsker-Aspen, & Primavera, 2009). We would expect that those who have healthier self and interpersonal functioning capacities would lead to better coping capacities and overall functioning.…”
Section: Discussionsupporting
confidence: 88%
“…The current study is distinctive in that it is the first to use ratings from inpatient unit therapists and data from the patient's chart to examine the construct validity of the SCORS-G. Previous studies have found that SCORS-G ratings are positively correlated with measures of adaptive functioning (Defife et al, 2013; Stein, Hilsenroth, Pinsker-Aspen, & Primavera, 2009), school performance, and peer relationships (Defife et al, 2013; Defife & Westen, unpublished data). Self and interpersonal functional impairments have been implicated in adolescents engaging in NSSI (Nock, 2010) and eating disordered behavior (Cross, Westen, & Bradley, 2011).…”
mentioning
confidence: 99%
“…The GARF is an instrument that allows a clinician to assess relational functioning of the family, and others have suggested that this particular feature be examined more frequently during treatment of mental health [38].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these propose an overall assessment of quality of relationship, such as the Parent Infant Relationship Global Assessment Scale (Aoki, Zeanah, Heller, & Bakshi, ) for younger children and their caregivers and the Global Assessment of Relational Functioning Scale for families with children of all ages (Group for the Advancement of Psychiatry Committee on the Family, ). These have shown good psychometric properties and clinical utility (Dausch, Miklowitz, & Richards, ; Denton, Nakonezny, & Burwell, ; Stein, Hilsenroth, Pinsker‐Aspen, & Primavera, ), but have not been utilized in epidemiological or clinical research. There are different techniques for standardized observations, as well as some existing and well‐validated parent report measures to identify PCRP (see, e.g., Biringen & Easterbrooks, ; Slep & Tamminen, ).…”
Section: Need For Reliable Assessment Of Parent–child Relationshipsmentioning
confidence: 99%